Sustainability and marketing in tourism: its contexts, paradoxes, approaches, challenges and potential - Font, Xavier; McCabe, Scott (Taylor & Francis, 2017)
Tourism marketing has typically been seen as exploitative and fuelling hedonistic consumerism. Sustainability marketing can, however, use marketing skills and techniques to good purpose, by understanding market needs, designing more sustainable products and identifying more persuasive methods of communication to bring behavioural change. This article summarises the latest research on the theories, methods and results of marketing that seeks to make tourist destinations better places to live in, and better places to visit. It explores sustainability marketing's two fundamental approaches, that of market development, using market segmentation, and that of sustainable product development. It introduces a Special Issue of the Journal of Sustainable Tourism on sustainable marketing, sharing evidence on the motivations, mechanisms and barriers that businesses encounter, and on successes in changing consumer behaviour and pursuing sustainability goals. Particular attention is given to the methodologies of sustainable tourism marketing, to the subject's breadth and complexity, and to its many innovations. Further research is called for to fully understand what contextual aspects influence these pro-sustainability interventions to achieve which outcomes in other settings, in order to validate some of the exploratory studies discussed, and establish the feasibility of scaling up pilot studies for more general use.